(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was designed to investigate Strongyloides stercoralis infestation in four selected slum areas of Dhaka city. Harada-Mori culture was applied for detection. The average prevalence of S. stercoralis infection was 13.42%; 11.77% in male and 13.85% in female. The highest prevalence was found (40%) among the slum dwellers aged 50-59 years old following the age group 10-19 years (16.66%). In summer, the prevalence was the lowest (2.50%) and the peak was in rainy season (33.33%). The infestation was significant (p<0.05) depending on the educational status, economic condition and sense of hygiene among the slum residents. Noticeable prevalence was observed among the dwellers living in mud floored house (40.91%), performing irregular nail trim (50%), day laborer (31.58%) and bare footers (24.24%). Positive history of diarrhoea showed higher prevalence (18.52%) of S. stercoralis. The results of the present study suggest that, in the urban slum community, changes in the household environment, promulgation of proper hygiene knowledge amongst the slum dwellers would lessen the transmission of S. stercoralis infection. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 199-203